Shifting the Paradigm: A Vizir’s Persian Handbook of Āyurveda in Sixteenth-century India - Speziale, Fabrizio (History of Science in South Asia, 2024)
The Ma‘dan al-šifā’-i Sikandar-šāhī is an extensive Persian handbook of Ayurvedic medicine made for Miyān Bhuwa ibn Ḫawāṣṣ Ḫān, a vizir of Sultan Sikandar Lōdī (r. 1489-1517) to whom the book was dedicated. This treatise was thought to provide Indian Muslim physicians, unfamiliar with Sanskrit, with a comprehensive manual of Ayurvedic medicine and therapy. Miyān Bhuwa allocated considerable resources to achieving this translation project and hired scholars to translate the many parts of Ayurvedic books used to compile the Persian text. This article explores the reasons behind the production of the Ma‘dan al-šifā’ and proposes a new reading of this book. It argues that Miyān Bhuwa’s project was part of a broader process of incorporation of Ayurvedic materials within Persian texts which had already started about two centuries earlier and which allowed Muslim physicians to master new forms of interpretation, classification and treatment of diseases when compared with earlier Arabic and Persian medical books. It looks at the epistemic and the practical issues raised in the preface of the Ma‘dan al-šifā’, which directly questions the adequacy of how Greco-Arabic thought understood body temperament in the Indian environment. It inquires into the authorship of this Persian Ayurvedic handbook and suggests that probably Miyān Bhuwa only assembled the translations made from Sanskrit texts. The last part of the article looks at the conceptual structure of the Ma‘dan al-šifā’ and how the Sanskrit sources and their models shaped the organization of the sections of the Persian book. Moreover, it suggests that the overall framework of the book relied on the overlap of models of presentation of medical knowledge, a device meant to negotiate between the models of the Sanskrit sources and those of the Muslim readers.